Implantação do matriciamento nos serviços de saúde de Capivari The implementation of specialist orientation in the health services of Capivari - Elizaete da Costa Arona (Universidade de São Paulo, 2009)
Capivari é um município de pequeno porte, localizado a 140 km da capital paulista, com população estimada em 43.779 habitantes (IBGE, 2007). A rede de Atenção Básica é composta por duas UBS, três ESF e uma Unidade Mista. O Matriciamento teve seu início em agosto de 2007, envolvendo quatro unidades de saúde com participação de duas especialidades: a Psicologia e a Fonoaudiologia. Posteriormente, com a ampliação da equipe de especialistas, passou a contar com toda a rede de Saúde Mental (Psicologia, Terapia Ocupacional, Caps II e Caps Ad), Serviço Social, Farmácia, Ambulatório de DST/Aids, Vigilância Sanitária, Vigilância Epidemiológica, Educação Física e Odontologia. O objetivo da proposta foi implantar na Atenção Básica um projeto de intervenção na gestão local sob o olhar do gestor municipal, buscando garantir às equipes das UBS maior apoio quanto à responsabilização do processo de assistência, garantindo a integralidade da atenção em todo sistema de saúde, procurando implementar mudanças de programas e ações que descentralizassem o acesso à especialidade, bem como disponibilizar recursos e equipamentos para viabilizar a proposta. As etapas de implantação foram: reuniões com as equipes envolvidas; aquisição de dois automóveis; contratação de novos profissionais, ampliação das especialidades envolvidas e capacitação das equipes. Como resultado foram observados o alargamento da participação de diferentes especialistas na Atenção Básica; a ampliação da resolubilidade das equipes; a definição do fluxo de encaminhamento; a abertura de um canal de comunicação interprofissional e o estabelecimento de um espaço de cogestão. Capivari is a city of small size, situated 140 km far from São Paulo, with a population estimated at 46,824 inhabitants (IBGE, 2007). The Primary Health Care network is composed of 2 UBS (Primary Health Care Units), 3 ESF (Family Health Strategy Units) and 1 Mixed Unit. The Specialist Orientation began in August 2007, involving 4 health units with the participation of two specialties: Psychology and Speech Therapy. Later, with the expansion of the team of experts, it included the entire network of Mental Health (Psychology, Occupational Therapy, and the Psychosocial Care Centers known as CAPS II and CAPS Ad), Social Work, Pharmacy, STD/AIDS Clinic, Health Surveillance, Epidemiological Surveillance, Fitness and Dental Health. The objectives of the proposal were: to implement a project in Primary Health Care for intervention in the local management under the view of the municipal manager; to provide, for the UBS teams, greater support regarding the accountability of the assistance process; to ensure integral care throughout the health system; to introduce changes into programs and actions to decentralize the access to specialists; and to provide resources and equipment to make the proposal real. The stages of deployment were: meetings with the teams involved; purchase of 2 cars; the hiring of new professionals; expansion of the specialties involved; and training of the teams. The results have been the enlarged participation of various experts in the Primary Health Care network, the increase in the teams' capacity to solve problems, the definition of the referral flow, the opening of an inter-professional communication channel and the establishment of a co-management space.